Morphofunctional efficacy of Phyllanthus amarus alkaloid extract on semen quality, hormonal profile and gonadal histomorphometric status in Plasmodium berghei-induced mice - Evelyn Tarela Ojugbeli; Solomon Ugochukwu Okom; Bartholomew Chukwuebuka Nwogueze; Pere-Ebi Yabrade Toloyai; Innocent Onyesom (Food Chemistry Advances)
The mainstay for malaria treatment is drug, but currently, the treatment is failing and making malaria infection worrisome. The alkaloid extract of the plant Phyllanthus amarus has been demonstrated to possess antimalarial activity. This present study evaluated the changes in semen quality, hormone profile and gonadal histomorphometric features in Berghei-induced mice treated with alkaloid extract of Phyllanthus amarus. Thirty-six BALB/c mice were divided into six groups (n=6 per group). The first two groups were positive (not infected, not treated) and negative (infected, but not treated) control mice, while the remaining groups (Groups 3–6) were the experimental mice infected with Plasmodium berghei (NK 65) malaria parasite and respectively treated with standard drug Lonart® DS (20 mg/kg) with 75 mg/kg, 150 mg/kg and 225 mg/kg of the Phyllanthus amarus alkaloid extract (PAAE) for 4 days. Then, 10 days later, the animals were euthanized and blood samples were collected for biochemical investigation. Testes tissues were harvested for histological assessment and semen samples were collected for analysis using standard procedures and documented methods. Data from our study revealed that Plasmodium berghei malaria-induced infection significantly (p<0.05) increased testicular hormones of testosterone and luteinizing hormone levels were significantly (p<0.05) reduced, semen quality were compromised and the microstructural architecture of the testes were distorted. However, treatments with the graded doses of PAAE protected the gonads, improved semen quality and restored the hormone levels in a dose-dependent manner and in pattern that compared favourably with the mice treated with standard drug of Lonart® DS. Alkaloids of Phyllanthus amarus are promising as antimalarial agent. Therefore, the active antimalarial alkaloid compounds of Phyllanthus amarus should be identified for further study.